2020
DOI: 10.1016/j.breast.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

First-line bevacizumab and eribulin combination therapy for HER2-negative metastatic breast cancer: Efficacy and safety in the GINECO phase II ESMERALDA study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Recent studies have focused on the combination of eribulin and targeted agents, including anti-HER2 agents, 23 poly ADP-ribose polymerase inhibitors, 24 immune checkpoint inhibitors, 25 and anti-angiogenesis agents. 26 Investigators have applied these novel combinations in patients in clinical practice, based on tumor subtypes and gene signatures. More than one-fifth of patients treated with the combination of eribulin and bevacizumab showed prolonged PFS compared to those treated with eribulin monotherapy; a similar conclusion was reached in the E2100 trial of paclitaxel plus bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the combination of eribulin and targeted agents, including anti-HER2 agents, 23 poly ADP-ribose polymerase inhibitors, 24 immune checkpoint inhibitors, 25 and anti-angiogenesis agents. 26 Investigators have applied these novel combinations in patients in clinical practice, based on tumor subtypes and gene signatures. More than one-fifth of patients treated with the combination of eribulin and bevacizumab showed prolonged PFS compared to those treated with eribulin monotherapy; a similar conclusion was reached in the E2100 trial of paclitaxel plus bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, eribulin has been investigated in combination with various targeted drugs including antiangiogenic agents, anti-HER2 agents and immune checkpoint inhibitors and other chemotherapeutic agents. 21,22 In this real-world study, we demonstrated the effectiveness and safety of eribulin-based therapy in heavily pretreated Chinese patients and provided data on the impact on QoL of eribulin-based therapy.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, most studies of bevacizumab on MBC are aimed at first-line treatment [ 20 , 21 , 22 , 23 , 24 , 25 ]. Three classic phase 3 studies have shown that compared with chemotherapy alone, bevacizumab combined with chemotherapy as first-line treatment can significantly prolong the PFS of MBC patients but fails to improve the OS [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%